STRATEGI MEDIA RELATIONS HUMAS PEMERINTAH KABUPATEN TAPANULI UTARA UNTUK MENINGKATKAN CITRA POSITIF - Redianto Sinaga; Suwardi Suwardi; Dayana Dayana (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2020)
The purpose of this study is to find out how media relations strategies are applied in media relationships, barriers faced in running the media relations strategy and the relationship model created between the PR with the media. This research uses the paradigm of kontruktivisme with qualitative descriptive approach. Data collection techniques were conducted through in-depth interviews, participatory observation, and document collection / library study. The result of this research shows the effort of Public Relations Division of North Tapanuli Regency Government to do the strategy to manage the relationship, develop the strategy and develop the network as an effort to improve the positive image. However, Media Relations strategy implemented by Public Relations of North Tapanuli regency is still less effective because some of the problems faced.